From Likert-type Scale to Likert-like Scale - Phonman, Ronnagrit; Kajitnatitham, Maleerat (Journal of Social Sciences in Measurement Evaluation Statistics and Research, 2024)
The Likert-summated rating scale is a research tool widely used by social and behavioral science researchers in Thailand. However, this instrument still exhibits several weaknesses and raises interesting notions that academics have introduced to guide the development of Likert-based estimation scales towards greater efficiency. Therefore, this article will present the main points regarding the Likert-type Scale and the issues that should be considered to improve and develop the scale into a Likert-like Scale, covering 5 key issues: 1) Whether the Likert-summated rating scale is an ordinal or interval scale, 2) Whether a 5-point rating scale is sufficient for measurement, 3) Whether the rating scale should have equal intervals and balanced response choices, 4) Whether the rating scale’s response choices should be even or odd, and 5) How to define the level or intensity of feelings in the rating scale. The discussion of each issue in this article is not prescriptive for readers. Instead, it may serve as a guideline for designing rating scales that are appropriate for the context and beneficial for developing research quality to ensure internal validity, as well as for enhancing the efficiency of rating scales.